Socio-economic related differences in the use of variation sets in naturalistic child directed speech: a study with argentinian population - Rosemberg, Celia Renata (2019)
Child-directed speech (CDS), compared to speech between adults, shows a higher amount of repetitiveness, particularly of sequences of utterances with self-repetitions. This phenomena, known as variation sets, has been found to be beneficial for learning. Although previous findings indicated socio-economic status? (SES) effects on the quantity of variation sets, they were based on data from child-parent dyadic interactions in play situations. Given that SES comprises interrelated factors affecting children?s quotidianity, here we examine SES effects on the use of variation sets in long recordings of the family naturalistic environment of 30 low and middle SES Argentinian children (8 to 20 months). Variation sets were automatically extracted from CDS provided by all the participants. Results demonstrated the effects of two factors related to SES-differences: while parent?s education showed a positive relation to the quantity and extension of variation sets, the number of people living in the household influenced it negatively.